Integration of Local Potential of Way Kambas National Park in Developing HOTS-Based Assessment Content in Biological Conservation Courses - Alma Aliya Jacinda; Siti Sriyati; Rini Solihat (Jurnal Penelitian Pendidikan IPA, 2024)
The assessment of Higher Order Thinking Skills (HOTS) based on local potential has not been widely used in biological conservation education. Assessments like this aim to encourage students to think critically, analytically, and creatively, as well as familiarize students with solving problems in real contexts, especially in the conservation area of Way Kambas National Park (WKNP) in Lampung. This study aims to identify the local potential of WKNP conservation areas that have the potential to be integrated with the development of HOTS-based assessments in the Biological Conservation Course. The method used in this study is descriptive with a qualitative approach. Interviews were conducted with 6 informants. Triangulation techniques and data interpretation then analyzed the data obtained. The results of this study show that there is a lot of local potential in WKNP conservation area that has the potential to be integrated into the assessment content on 7 biological conservation materials that can be made HOTS-based assessments to hone students' high-level thinking skills.